Concurrent infections of cells by two pathogens can enable a reactivation of the first pathogen and the second pathogen's accelerated T-cell exhaustion. Issue 12 (December 2022) - Roe, Kevin
Abstract: When multiple intracellular pathogens, such as viruses, bacteria, fungi and protozoan parasites, infect the same host cell, they can help each other. A pathogen can substantially help another pathogen by disabling cellular immune defenses, using non-coding ribonucleic acids and/or pathogen proteins that target interferon-stimulated genes and other genes that express immune defense proteins. This can enable reactivation of a latent first pathogen and accelerate T-cell exhaustion and/or T-cell suppression regarding a second pathogen. In a worst-case scenario, accelerated T-cell exhaustion and/or T-cell suppression regarding the second pathogen can impair T-cell functionality and allow a first-time, immunologically novel second pathogen infection to escape all adaptive immune system defenses, including antibodies. The interactions of herpesviruses with concurrent intracellular pathogens in epithelial cells and B-cells, the interactions of the human immunodeficiency virus with Mycobacterium tuberculosis in macrophages and the interactions of Toxoplasma gondii with other pathogens in almost any type of animal cell are considered. The reactivation of latent pathogens and the acceleration of T-cell exhaustion for the second pathogen can explain several puzzling aspects of viral epidemics, such as COVID-19 and their unusual comorbidity mortality rates and post-infection symptoms. Abstract : T-cell exhaustion; Accelerated T-cell exhaustion; T-cell suppression; Viral infections; Bacterial infections; Protozoan infections.